Pendidikan Agama Kristen Di Era Disrupsi: Peluang Inovasi “Blended Learning” Di Sekolah Dan Gereja - Dyulius Bilo (STT Pelita Dunia, 2021)
Abstract: This research to describe how Christian Religious Education in the Era of Disruption make use of the “Blended Learning” innovation opportunities in schools and churches. This research uses a descriptive qualitative approach that refers to efforts to describe, explain, and describe a phenomenon that occurs in the social environment. The phenomenon that we want to describe here is related to the disruption in every area of life that cannot be avoided and rejected, including in the world of religious education. Disruption by many experts is a change because off technological innovations that not only affect a person's mindset but have also had an impact on the theory and practice of human life. Disruption as a necessity that brings progress and welfare of human life. Christian Religious Education is efforts made by believers, servants of God (teachers, evangelists, pastors) and the church in the guidance of the Holy Spirit to introduce Jesus Christ and lead each individual to believe, love, and serve Jesus as Lord and his Savior. The findings of this research are that the era of disruption cannot be avoided and rejected, there have been many positive and negative effects of disruption, services off PAK learning in school and church must be disrupted if it is to survive and continue to exist as an effort to preach the gospel of Christ.